Poverty, Race and Gender Inequalities in Intersection, Salvador, Brazil - Gomes, Cristina (Advances in Social Sciences Research Journal, 2017)
“The central question of this research concerns how poverty is related to 7 familial and social conditions and, in particular, to sex and the self-declaration of color. Relations between groups would be the source of prejudice; gender discrimination and racism can be understood within the framework of intergroup competition for scarce resources (Maslow 1942; Sherif et al 1966), according to the perspective of realistic intergroup conflicts (Campbell 1965, 1965a) or Tajfel’s (1983 pp.305) theory on prejudice as a symbolic competition in relations between categorizations, social asymmetries and discrimination. The quantitative analysis is based on a database containing beneficiaries of social policies provided by the Ministry of Social Development and Hunger Alleviation, focusing on gender and race inequalities amongst poor people in the State of Bahia, Brazil. Data includes eight million individual people or three million families who have, at some time, applied for social policy benefits, and could currently be considered beneficiaries or potential beneficiaries. The factors related to poverty are analyzed focusing on families rather than individuals. Results show that social policies have been able to reduce the impact of poverty and race inequalities. However, racism operates in the society, since poverty - particularly extreme poverty - is more frequent and likely among households with indigenous, black and parda (mixed) heads of households, even after controlling other individual, familial and contextual factors. Heads of households with a lower educational level, female and young, indigenous, black and parda heads of households are likely to have poor or extremely poor families, particularly in the smaller municipalities”.